Parametric study of ductile moment-resisting steel frames A first step towards Eurocode 8 calibration. - Sanchez-Ricart, L. (Earthquake engineering & structural dynamics.)
A parametric study of 13 608 ductile moment-resisting steel frames designed according to Eurocodes 3 and 8 is performed. A flowchart for the evaluation of the seismic-resistant capacity of the designed frames is developed based on the N2 method. The design structural overstrength, ductility supply, plastic redistribution parameter, supply reduction factor and performance ratio of the frames are analysed. We determine that the frames have performance ratios higher than 1, mostly due to high values of design structural overstrength, showing that the seismic supply produced by the restraints of Eurocodes 3 and 8 is always higher than the seismic demand.